K. in Baltimore. Narrative Similarities between The Wire and The Castle - Cotarelo Comerón, David (2019)
This paper studies the narrative similarities between the novel The Castle by Franz Kafka and the TV series The Wire, created by David Simon for HBO. We analyze the main characters in each work, K. in The Castle and Jimmy McNulty in The Wire, as antiheroes that fight against the bureaucracy of the institution they work for. Also, we find other connexions between both works in aspects like the socio-historical context, the presence of an opaque and strongly hierarchized power, as well as analogies in the representation of institutions and the individuals who face them.